2018
DOI: 10.3390/app8112163
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the Experimental Results of a Parabolic Trough Collector (PTC) Solar Plant to an Absorption Air-Conditioning System

Abstract: The present study reports the experimental results of a parabolic trough collector field and an absorption cooling system with a nominal capacity of 5 kW, which operates with the ammonia-lithium nitrate mixture. The parabolic trough collectors’ field consists of 15 collectors that are made of aluminum plate in the reflector surface and cooper in the absorber tube, with a total area of 38.4 m2. The absorption cooling system consists of 5 plate heat exchangers working as the main components. Parametric analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Hence, there are other working fluids which may consider as an alternative approach, but LiBr-H2O is very common and easily available. [60,61] 5.2.2 Parabolic Dish Collector. -Parabolic dish collector is another type of concentrating collector which focus the beam of light on a focal point where receiver is installed.…”
Section: Parabolic Troughmentioning
confidence: 99%
“…Hence, there are other working fluids which may consider as an alternative approach, but LiBr-H2O is very common and easily available. [60,61] 5.2.2 Parabolic Dish Collector. -Parabolic dish collector is another type of concentrating collector which focus the beam of light on a focal point where receiver is installed.…”
Section: Parabolic Troughmentioning
confidence: 99%
“…The main advantages of these systems are how: (i) natural refrigerants, usually water, is used, and (ii) the driving force is low-grade thermal energy, such as solar thermal energy and industrial waste heat. Solar cooling with a combination with absorption refrigeration was investigated by Galindo Luna et al [14] and Li et al [15]. In addition, Wang et al [16] studied the dynamic behavior of an absorption chiller under various operating conditions.…”
Section: Next Generation Heat Pump/refrigerationmentioning
confidence: 99%
“…In this period, several configurations have been studied and analyzed in terms of stages, absorberrefrigerant pairs, drive medium, applications and cooling capacities. In the literature, studies of solar cooling thermal systems have been found with single-effect absorption machines and driven by various types of solar collectors: with nonconcentrating or stationary solar collectors [4,5,6,7,8,9,10,11,12,13,14,15,16], with parabolic cylinder collectors [6,14,17,18] and with linear Fresnel collectors [19]. Also, systems with absorption machines with two or more stages and with various types of solar collectors: with parabolic cylinder collectors [4,20] and with linear Fresnel collectors [21].…”
Section: Introductionmentioning
confidence: 99%